Sintesis Komposit Kampas Rem Bebas Asbes Berpenguat Serbuk Kulit Singkong - Widya Emilia Primaningtyas; Rahma Rei Sakura; Amir Biqi; Chamim Handoyo (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2018)
An agricultural waste production in Indonesia is increasing as well as the growth of agricultural production. This has become a serious problem in Indonesia. A massive waste will have a negative impact on the health of living things. Therefore, this study aims to provide solutions for the utilization of agricultural waste for the needs of the industry in the automotive sector. In addition, the use of agricultural waste, especially cassava peel waste, can be used as a substitute for brake pads in the form of composite reinforced natural fibers. There are two conditions for cassava peel waste, carbonized and uncarbonized. 50,80,100 Mesh particle size of cassava peel powder used. The composition of the ratio of volume fraction between cassava peel powder and composite epoxy resin used are 20:80; 30:70; and 40:60. The results show that variations in the composition of fibers and resins have an impact on wear values. The best wear resistance shown from the added of 20% cassava peel powder in 100 mesh sizes of particle with 0,00061 ± 0,00039.